Losing their Turf: horse racing ends in Singapore - Sng, Eunice Hui Ying (Nanyang Technological University, 2024)
The Singapore Turf Club (STC) will hold its final event in October 2024 after over 180 years of bringing horse racing to the public. Despite its long legacy, mainstream audiences have lost interest in the sport and its most ardent spectators are dwindling seniors. Horse racing has been sidelined due to its image of vice and lack of publicity.